Effect of 1wt%Zn Addition on Microstructure and Mechanical Properties of Mg-6Er Alloys under High Strain Rates - Hui Yu; Junchao Ren; Shaoming Kang; Wei Yu; Zhifeng Wang; Jianhang Feng; Qingzhou Wang; Puguang Ji; Xin Zhang; Fuxing Yin (Metals, 2022)
In this study, we investigated the high strain rate response of Mg-6wt%Er alloys with 1wt%Zn addition by split Hopkinson pressure bar (SHPB) tests in a range of 900–2500 s−1. Their related microstructures were also characterized by optical microscopy (OM), scanning electron microscopy (SEM), electron back-scattering diffraction (EBSD), and transmission electron microscopy (TEM). In particular, the twinning and stacking faults (SFs) in Mg-6Er and Mg-6Er-1Zn alloys are characterized, and the interactions between twin/SFs and dislocations are analyzed in detail. Compared with twins, the dispersed and dense SFs seem to more readily interact with dislocations, resulting in the enhancement of the strength of alloys. Especially at a high strain rate of 1450 s−1, dislocations are prone to tangle around the twins and SFs, forming low-angle grain boundaries (LAGBs). The addition of Zn in Mg-6Er can make LAGBs more easily transform into high-angle grain boundaries (HAGBs) due to the existence of SFs.